Análisis de la información de responsabilidad social divulgada por entidades financieras en Argentina - Pastor, Sandra Patricia (Ediciones UNL. Secretaría de Extensión de la UNL, 2020)
This work presents the progress of the results of the research project (2017/2019) regarding the nature and scope of the relationship between Social Responsibility (SR) and the SR information disclosed by financialentities in Argentina.Various theories that study the disclosure of corporate information assume that, in particular circumstances, companies disclose more information when the expectations of the cost-benefit ratio are favorable.However, each organization has special features which have an influence on their disclosure strategies.Previous research works (Haro del Rosario et al., 2012; González Fernández, 2012; Pérez-Ruiz y Rodríguez del Bosque, 2012) have analyzed the factors which determine the disclosure of SR information in Spanishfinancial institutions.The methodology applied is descriptive and, based on a qualitative and quantitative methodological theoretical approach, sustainability reports (qualitative) are analyzed and the factors which determine the voluntary disclosure of SR information are studied, following linear regression statistical models.Based on the analysis of the amount of information disclosed in relation to the most significant factors which determine the disclosure of information, the profile of the organizations that issue SR information can be observed. In order to do this, and by virtue of the hypotheses proposed, a global disclosure index was used, which is disaggregated into the three integral aspects of CSR: economic disclosure index, environmental disclosure index and social disclosure index.  The results obtained are consistent with previous studies (Gamerschlag et al., 2011) and they show a positive relationship between the amount of CSR information disclosed and a greater visibility of the company, agreater variety of shareholders and the audit of CSR reports. On the other hand, its relationship with profitability is inverse.